The future of the book - Díaz Sánchez, Nicolás (2005)
I will begin my appreciation with a quote referred to by James O'Donnell -corresponding to the novelist E. Annie Proulx-, which is also frequently recorded by the authors included in this compilation: "No one is going to sit down to read a novel in a ridiculous little screen. Never."